PUBLIC PARTICIPATION IN CONSTITUTIONAL AMENDMENTS: A COMPARATIVE ANALYSIS OF INDONESIA AND THAILAND - Masykuri, Masykuri; Rustan, Ahmad; Ichlas, Rudy Iskandar; Umar, Wahyudi (Universitas Syiah Kuala, 2024)
The idea of revising the 1945 Constitution is likely to spark debate. Nevertheless, Article 37 of the 1945 Constitution has provided a mechanism for amendment, rather than replacement, of the constitution. The amendments to the 1945 Constitution are now mandatory, as previously decreed by the MPR leadership, which will be continued by the current leadership. This paper examines the role of public participation in the amendment of constitutions in Indonesia and Thailand. The study employs a normative legal research approach, utilizing statutes, conceptual frameworks, and comparative analyses. Data was collected from books, academic journals, relevant laws, and regulations. The results indicate that the forms of public participation in Indonesia and Thailand in the constitution-making and amendment processes are largely similar, including public hearings, working visits, socialization, seminars, workshops, and discussions. However, a notable difference exists in that Indonesia lacks explicit provisions for public participation in its constitutional amendment process, whereas Thailand has established clear regulations. It is recommended that Indonesia clearly regulate public participation as a procedure in its constitution-making and amendment processes.